NEEDS ANALYSIS FOR THE DEVELOPMENT OF A PROBLEM-SOLVING TEACHING MODULE FOR SPECIAL REMEDIAL MATHEMATICS (PSTM) - Hj Rosli, Nurul Majdiah; Ali, Siti Rahaimah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study is part of a needs analysis for developing the Problem-Solving Teaching Module for Special Remedial Mathematics (PSTM), targeting remedial mathematics students in Level 2 of primary school. The research focuses on understanding the necessity of such a module among educators. Data collection involved 100 remedial and primary school mathematics teachers in the Petaling Perdana district, Selangor, using purposive sampling and a questionnaire with five Likert-scale items. The quantitative analysis, conducted using SPSS version 25, employed descriptive statistics to assess mean values and percentages. Results revealed a high demand for the module, with a mean score of M=4.49 and 99% of respondents supporting its development. These findings will guide the design and development of the PSTM in subsequent phases. The study provides foundational insights into aspects that need emphasis, such as the integration of the Understanding Numeracy Level Model for Primary School (UNLMPS). Teachers strongly endorsed the need for the module, citing its potential to clarify and enhance the structure of problem-solving activities tailored to the capabilities of remedial students. The study’s implications offer guidance for researchers in developing an effective module that aids Stage 2 remedial students in mastering essential mathematical problem-solving skills.